Preoperative Super-Selective Embolization versus “On-Clamp” Laparoscopic Partial Nephrectomy for T1 Renal Tumors— A Prospective Randomized Study (Journal of Kidney Cancer, 2024)
To analyze and compare the intraoperative and post-operative outcomes of “on-clamp” laparoscopic partial nephrectomy (LPN) with “preoperative super-selective angioembolization” before LPN. This randomized clinical study was conducted at Gauhati Medical College Hospital, Guwahati, India, between November 2021 and November 2023. Adult patients of either gender diagnosed with T1 renal tumors were included in the study. All patients underwent diethylenetriamine pentaacetate scan preoperatively and at 1-month follow-up. The patients were randomized using a parallel group design with an allocation ratio of 1:1 to receive either preoperative angioembolization followed by LPN or conventional “on-clamp” LPN. Demographic and baseline parameters were recorded along with pre- and post-operative data. There was no significant difference between the two groups in terms of age (P = 0.11), gender distribution (P = 0.32), body mass index (P = 0.43), preoperative hemoglobin (P = 0.34), and preoperative estimated glomerular filtration rate (eGFR; P = 0.64). One patient in the embolization group required radical nephrectomy because of accidental backflow of glue into the renal artery during embolization whereas four patients required clamping due to inadequate embolization. Preoperative super-selective embolization yielded significantly less blood loss, compared to “on-clamp” LPN (145 [50.76 mL] vs. 261 [66.12 mL], P < 0.01). There was no significant difference between post-operative eGFR (at 1 month) between the two groups (P = 0.71). Preoperative embolization offers improved outcomes in the dissection plane, total operative time, and blood loss, compared to conventional “on-clamp” LPN but has no significant effect on change in eGFR.